Investigation of level density and Gama strength function for photoneutron reaction in medical linacs in Beamline - Oflaz, U.; Sarpun, I. H.; Ozdogn, H. (Pergamon-Elsevier Science Ltd, 2022)
Photoneutron reaction cross-sections of Au-197, Re-187, W-186, Ta-181, Mo-94,Mo-95,Mo-96,Mo-97,Mo-98,Mo-100 isotopes were calculated through the TALYS 1.95 nuclear reaction code. The energy range of the incident photon chosen as 7 MeV-30 MeV corresponded to the range of the giant dipole resonance region, which is also an applicable energy range in radiotherapy for many commercial medical linear accelerators. Calculations were performed using three phenomenological level density models available in code, namely the Constant Temperature Fermi Gas Model, the Back-shifted Fermi Gas Model, and the Generalized Superfluid Model. The most convenient level density model for each reaction was chosen using relative variance calculations. The cross-section calculations were repeated using gamma strength function models, Kopecky-Uhl generalized Lorentzian model, Brink-Axel Lorentzian model, and Goriely's hybrid model and the best level density model was kept constant. The calculated data and the experimental data from the international Experimental Nuclear Reaction Data Library were analysed and compared graphically.
Keywords: Photoneutron; Cross; Section; Medical linac head; Level density; Gamma strenght function; EXFOR